O potrzebie opracowania koncepcji i metody szacowania struktury ludności bez zniekształceń i zakłóceń - Valkovics, Emil (Wydział Prawa i Administracji UAM, 1981)
The interpretation of age-pyramids representing population structures qualified as distorted may be found mostly in the form of specifying the causes of „cuts" and „protrusions" seen on them, without taking their multiplying effects exerted mostly on the number of birth into consideration. The calculation of age-pyramids or population structures referring to identical dates of observation necessitates to eliminate the effects deemed as causing distortions, occured extraordinarily during the century preceding the observation of the population on the life history of each of the birth cohorts (generations) constituting the population. After calculating (estimating) the population sùrplusses or losses regarded as extraordinary, as well as their structures, we have to elaborate the hypotheses on mortality, nuptiality, fertility and external migration of their — and of their descendants — further lives. Afterwards, on the basis of fictive numbers of the populations of the related birth cohorts for the termination of the effects causing distortions up to the date of the observation „population projections" are to be realized. The age-pyramid and population structure without distortion may be compared with the real (distorted) age-pyramid and population structure in several ways. The calculation of the structure of subpopulations without any perturbation — constituting the population — necessitates also the elimination of the effects of differences in the mortality and external migration of the subpopulations, beyond the so-called rectangular standardization of the age-specific rates of the subpopulation observed transversally. If it is not possible, we have to apply the hypotheses of independency and continuity. However, neither the elimination of the effects of differences observable in the calendar within the individual cohorts concerning the longitudinal sums of the age specific rates of subpopulations can be neglected. Beyond the transversal population structures without any distortion and perturbation, also their longitudinal versions referring to individual birth cohorts (generations) can be calculated, as they are in interrelation with the transversal versions of the former one, that may be described also in mathematical way.
On the Need of Elaboration of the Concept and Method of Population Structure Calculation Without Distortion and Perturbation